1999
DOI: 10.1074/jbc.274.9.5823
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Processing of the Alzheimer's Disease Amyloid Precursor Protein within Its Cytoplasmic Domain by Caspase-like Proteases

Abstract: Alzheimer's disease is characterized by neurodegeneration and deposition of ␤A4, a peptide that is proteolytically released from the amyloid precursor protein (APP). Missense mutations in the genes coding for APP and for the polytopic membrane proteins presenilin (PS) 1 and PS2 have been linked to familial forms of early-onset Alzheimer's disease. Overexpression of presenilins, especially that of PS2, induces increased susceptibility for apoptosis that is even more pronounced in cells expressing presenilin mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
96
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(101 citation statements)
references
References 50 publications
(56 reference statements)
4
96
0
1
Order By: Relevance
“…Later it was shown that APP is degraded in lysosomes to amyloidogenic and nonamyloidogenic fragments Haass et al 1992). In addition, APP was shown to be a caspase substrate (Weidemann et al 1999;Lu et al 2003), but the impact of this processing on Ab generation and/or AD pathology is probably minor (Harris et al 2010). …”
Section: Degradation Of Appmentioning
confidence: 99%
“…Later it was shown that APP is degraded in lysosomes to amyloidogenic and nonamyloidogenic fragments Haass et al 1992). In addition, APP was shown to be a caspase substrate (Weidemann et al 1999;Lu et al 2003), but the impact of this processing on Ab generation and/or AD pathology is probably minor (Harris et al 2010). …”
Section: Degradation Of Appmentioning
confidence: 99%
“…A number of laboratories have recently demonstrated that APP can be cleaved in the cytoplasmic domain by caspases after the aspartate residue at position 664, Val-Glu-Val-Asp 664 2Ala, (APP 695 numbering, or Asp 720 using APP 751 numbering) (7)(8)(9)(10)(11)(12). This cleavage would generate a C-terminal-truncated APP molecule that is ϳ3.5 kDa shorter (APP⌬C31) (7,12).…”
mentioning
confidence: 99%
“…Each of the four caspases, 3, 6, 7, and 8, have been shown to cleave APP in in vitro assays, and a major caspase site has been identified at Asp-720 (VEVD), resulting in the release of a fragment containing the last 31 amino-acids of APP (C31) and the production of APP⌬C31 (lacking Ala 721 to Asn 751 ) (5)(6)(7)(8). Two other major caspase sites have been recently identified at the N-terminal domain of APP Asp 197 and Asp 219 , leading to the production of a ϳ90 kDa fragment (APP⌬N).…”
mentioning
confidence: 99%